Narratives of the Unspoken in Contemporary Irish Fiction Silences that Speak - Caneda-Cabrera, M. Teresa; Carregal-Romero, José (New Directions in Irish and Irish American Literature,, 2023)
This Open access book is a collection of essays and offers an in-depth analysis of silence as an aesthetic practice and a textual strategy which paradoxically speaks of the unspoken nature of many inconvenient hidden truths of Irish society in the work of contemporary fiction writers. The study acknowledges Ireland's history of damaging silences and considers its legacies, but it also underscores how silence can serve as a valuable, even productive, means of expression. From a wide range of critical perspectives, the individual essays address, among other issues, the conspiracies of silence in Catholic Ireland, the silenced structural oppression of Celtic Tiger Ireland, the recovery of silenced stories/voices of the past and their examination in the present, as well as millennial disaffection and the silencing of vulnerability in today's neoliberal Ireland. The book 's attention to silence provides a rich vocabulary for understanding what unfolds in the quiet interstices of Irish writing from recent decades. This study also invokes the past to understand the present and, thus, demonstrates the continuities and discontinuities that define how silence operates in Irish culture. M. Teresa Caneda-Cabrera is Senior Lecturer in English at the University of Vigo, Spain. She is the author of a monograph on A Portrait of the Artist as a Young Man and sits on the Editorial Board of European Joyce Studies. Her research on silence and vulnerability in contemporary Irish fiction has been funded by the Spanish MCIN, AEI and ERDF. She is the co-editor of Atlantic Communities: Translation, Mobility, Hospitality (2023) and the editor of Telling Truths: Evelyn Conlon and the Task of Writing (2023). José Carregal-Romero lectures at the University of Huelva, Spain. His research focuses on the intersections between gender and sexuality in contemporary Irish literature, with a keen interest in silence andvulnerability. He is the co-editor of Revolutionary Ireland, 1916-2016: Historical Facts & Social Transformations Re-Assessed (2020) and the author of Queer Whispers: Gay and Lesbian Voices of Irish Fiction (2021).